Do hotspots fall within protected areas? A Geographic Approach to Planning analysis of regional freshwater biodiversity. (5th September 2019) - Walters, Ashley D.; Brown, Madelyn A.; Cerbie, Gina M.; Williams, Marsha G.; Banta, Joshua A.; Williams, Lance R.; Ford, Neil B.; Berg, David J.
Abstract: Identification of biodiversity hot spots is necessary for developing conservation strategies. The south‐eastern U.S.A. harbours high aquatic biodiversity; however, this diversity is threatened as a result of anthropogenic activities. We report patterns of fish and mussel biodiversity, locate hotspots of diversity and endemism, and identify gaps in protection of these hotspots. Maxent was used to generate species distribution models for native fish and mussel species in river basins throughout east Texas. Stacked species distribution models were used to assess spatial patterns of biodiversity and examine the concordance between fish and mussel hotspots. A Geographic Approach to Planning analysis was used to identify areas of high conservation concern. Predicted geographical variation in species richness of mussels corresponds to patterns shown in fish; however, there was discordance among endemicity hotspots between the two taxa. Because overall endemicity was low in both groups, species richness is likely to be the more informative measure of biodiversity at these regional scales. While hotspots represent a small percentage of the study area, almost all richness and endemicity hotspots (>95%) in east Texas occur outside of protected areas. The results of this study suggest that protected areas designated based on terrestrial habitat may fail to protect aquatic biodiversity. Studies such as this provide a baseline for development of conservation and management strategies for protection of regional freshwater biodiversity, while also suggesting that designating conservation lands should include consideration of both terrestrial and aquatic biodiversity.